Avaliação da taxa de dessulfuração com injeção de CaO/CaF2 micropulverizada no forno panela - Willian Facundes (2019)
Increasing demand for low Sulfur steel has led some steelmakers to study ways to optimize desulphurization treatment in steel, with a view to reducing not only the Sulfur content but also the treatment time of the secondary refining steel. Given this, the practice of micropulverized mixture injection becomes an alternative that can meet these two longings. Therefore, this subject has been the subject of some studies, especially regarding the injection rate, desulphurizing agent particle size and reaction mechanisms involved in the process. In the present paper, predictive equations were developed to calculate the desulphurization mixture used in aluminum and silicon-killed steels (AS) and aluminum-killed steels (AA). Heats of both classes were performed to validate these equations. In addition to the mixture prediction as a function of the initial and objective Sulfur content, Sulfur prediction curves as a function of the injection time were determined. Sulfur removal by gas injection (lance) with average flow of 110 Nm3 / h was compared, a practice previously used in Usiminas and the gas + mixture. A comparison was also made between desulphurization using plug and it was found that the desulphurization rate obtained by gas injection and mixing was 78%, while with gas injection alone it was 22%. The use of the proposed mixture in the process resulted in a reduction of 1.1 kg / t micropulverized mixture, 0.22 kg / t aluminum, 3.3 kWh / t energy, 0.034 kg / t electrode and 2 minutes of treatment.